"Animals like us": revisiting organizational ethnography and research. Issue 3 (12th October 2015) - Wels, Harry
Abstract : Purpose: – Now that the human-animal distinction is increasingly critiqued from various disciplinary perspectives, to the point where some suggest even letting go of the distinction completely, the purpose of this paper is to argue that organizational ethnography should start to explore in more detail what this means for organizational ethnographic research, theory and analysis to include non-human animals in it. Design/methodology/approach: – Revisiting the author's earlier organizational ethnographic work in Zimbabwe on a private wildlife conservancy, an organization that was specifically set up for and around wildlife. At the same time these non-human animals were not taken into account methodologically nor featured at all in the empirical material or in the analysis. What could it mean for the analysis and conclusions if non-human animals would have been part of the equation? Findings: – Since we live in a world shared between human and non-human animals, this also is true for the organizational lives. As scientific research increasingly shows that the distinction between human and non-human animals is more in degree than in kind it is interesting to note that nevertheless non-human animals usually produce deafening "silences" in organizational ethnographic work. Revisiting the author's earlier organizational ethnographic work in this context the author shows how taking non-human animals on board of the analysis radically alters the outcomes of the research. Research limitations/implications: – This paper reports on revisiting the author's earlier ethnographic research, without actually doing the research itself again. In that sense it is a hypothetical study. Practical implications: – Organizational ethnography might have to rethink what it would mean in terms of fieldwork methodologies if it would allow non-human animals as actual agentic stakeholders in the research and analysis. It would at least need to also think in terms of "research methodologies without words" as non-human animals cannot be interviewed. Social implications: – The paper is based on a social justice perspective on human-animal relations. It tries to contribute to an intellectual argument to take non-human animals more seriously as "co-citizens" in the (organizational) life world. This may have wide ranging implications for the life styles, ranging from the types of food we eat, to liquids we drink, to the ways we think about the human superiority in this world. Originality/value: – A highly self-reflexive account of the author's earlier organizational ethnographic work, showing what it means theoretically if we take non-human animals seriously in organizational ethnographic research and analysis. At the same time it shows quite painfully organizational ethnography's speciecist approach to research methodologies and processes of organizing.